B254 Ultrasound guided continuous supraclavicular brachial plexus block using an intravenous cannula for post-traumatic finger reimplantation: a case report. (11th August 2022) - Joshi, R; Jeevan, R; Ramesh, J; Basheer, A
Abstract : Background and Aims: Continuous blockade of brachial plexus at the Supraclavicular level, for prolonged elbow and hand surgeries, is usually achieved by using catheters. But these are costly. A cost effective method would be intravenous cannulae. Methods: A 47 year-old ASA I male patient, was scheduled for finger re-implantation for traumatic loss of middle three fingers. He had lower respiratory tract infection. Patient refused for surgery under general anesthesia. He received premedication with Midazolam 1 mg and Fentanyl 30 microgram IV. Under ultrasound guidance, continuous supraclavicular brachial plexus block was performed using an intravenous cannula since patient could not afford a catheter. After 2% lignocaine infiltration, a 16 G IV cannula needle was inserted in-plane from lateral to medial direction and advanced to pierce sheath posterior to brachial plexus. The tip was positioned at the corner pocket and, 10 ml 2% Lignocaine with adrenaline, 10 ml 0.25% Bupivacaine and 4 mg Dexamethasone was slowly injected after intermittent negative aspiration. The cannula sheath was kept in situ. Intraoperatively Dexmeditomidine infusion was started. Injection 0.25% Bupivacaine 10 ml was repeated after 4 hours and 8 hours through the cannula. Results: Surgery lasted for 10 hours in supine position. Supraclavicular nerve block cannula was removed immediately after surgery. Postoperatively patient was on Paracetamol 1 gm IV Q8H. Patient was pain free throughout and postoperatively upto 6 hours. Conclusions: Intravenous cannula is a cost-effective, readily available and time saving alternative to catheter. It might be considered intraoperatively for continuous supraclavicular brachial plexus block in prolonged upper limb surgeries.